Gelatin from Doncella skin (Pseudoplatystoma fasciatum) and its use as an encapsulating material - Tello Célis, Fernando (2019)
Fish gelatin has gained increasing attention as an alternative to mammalian gelatin. However, the search for new sources with characteristics similar to commercial ones is still necessary. Due to this, the objective of this study was to obtain and characterize Doncella skin gelatin (Pseudoplatystoma fasciatum) and evaluate its use as an encapsulating material when producing microparticles by complex coacervation. Gelatin and gum arabic were used as wall materials and Mauritia flexuosa oil, as filler material. The Doncella skin gelatin was obtained by acid extraction and evaluated in terms of the aspects: yield, melting point; molar mass distribution; proximal composition; size, morphology, average particle diameter and encapsulation efficiency. The yield of the gelatin powder was ~ 20.03% per 100 g of wet skin, in addition, had a melting point of 29.1 ° C. The mean diameters reported were 117.40 μm ± 38.05 and 105.39 μm ± 37.93, when Doncella skin gelatin (MCGD) and porcine gelatin (MCGP) were used, respectively, with significant statistical differences (p <0.05). The encapsulation efficiencies obtained by the MCGD and MCGP systems were 88.45 ± 1.77 and 83.78 ± 4.44 respectively. In conclusion, we demonstrate the viability of the Doncella gelatin as an encapsulating material. But there is still a lack of research to guarantee the quality of gelatine. In this way, we highlight the potential of Doncella skin gelatin for uses in various areas.